An improved model for predicting performance of finned tube heat exchanger under frosting condition, with frost thickness variation along fin - TSO, C; CHENG, Y; LAI, A (2006)
Frost accumulation on a heat exchanger, a direct result of combined heat and mass transfer between the moist air flowing across a cold surface, causes heat transfer performance degradation due to the insulating effect of frost layer and the coil blockage as the frost grows. The complex geometry of finned tube heat exchangers leads to uneven wall and air temperature distribution inside the coil, and causes variations of frost growth rate and densification along the coil. In this study, a general distributed model with frost formation was developed. The equations for finned tube heat exchanger were derived in non-steady-state manner and quasi-steady state in the frost model. In order to make the model more realistic, the variation of frost along fin due to uneven temperature distribution was included. The presented model is able to predict the dynamic behavior of an air cooler both under non-frost and frost condition. Comparisons were made based on the frost mass accumulation,. pressure drop across coil and energy transfer coefficient, and results were found to agree well with reported experimental results. (c) 2005 Published by Elsevier Ltd.